PEMAHAMAN SYARIFAH HALIMAH ALAYDRUS TERHADAP AYAT-AYAT PARENTING DALAM KISAH NABI YUSUF : Analisis Hermeneutika Hans Georg Gadamer - Kholisah, Nur (STAI AL-ANWAR SARANG, 2022)
This article presents a study of Hans Georg Gadamer's hermeneutical analysis of the interpretation of parenting verses by Syarifah Halimah Alaydrus in the Study of Tafsir Surah Yusuf. Parenting is not explicitly mentioned in the Qur'an, but the stories in the Qur'an contain a lot of parenting knowledge. This research is studied to find out the educational teachings of the previous prophets, as well as the educational teachings of the descendants of the last prophets, and to get to know more closely the figure who conveys knowledge, namely Syarifah Halimah. Judging from Hans Georg Gadamer's theory related to fusion of horizons, awareness of being influenced by history, and application. The results of this analysis indicate that parenting in the story of Prophet Yusuf from Syarifah Halimah is to introduce the love of Allah and His Messenger to children through the love of parents to children, in the form of entrusting children to God's care. Parents always protect children from physical and mental evil according to what the Prophet taught. Syarifah Halimah's understanding was motivated by the close relationship with her parents, Psychology from her nephew, accustomed to studying the works of Imam al-Ḥaddād, following the habits of the Tarim mashāyikh, while at the pesantren he memorized hadith and the Qur'an. The implementation of Syarifah Halimah's explanation is to manifest love, in the form of calling the closest person with a favorite call, and punishing something in accordance with the applicable punishment in the place occupied.